2020
DOI: 10.1016/j.bpj.2020.07.035
|View full text |Cite|
|
Sign up to set email alerts
|

Endocytosis Is a Key Mode of Interaction between Extracellular β-Amyloid and the Cell Membrane

Abstract: Interactions between amyloid-b peptide (Ab) and the cell membrane include interaction with membrane lipids and binding to membrane receptors, both of which are considered to be the toxicity mechanisms of Ab. However, it is unclear whether both mechanisms lead to cytotoxicity. Thus, we aimed to analyze these two mechanisms of Ab42 interaction with cell membranes under different Ab aggregation states. To this end, model membrane experiments were conducted. Quantitative analysis of Ab42 monomers or oligomers boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The conclusions of this work were revealed to be of extreme importance to understanding the main mechanism implicated in AD pathogenesis since humans and macaque brains share significant similarities [ 18 ]. Additionally, the mechanistic studies performed in different neuronal cell lines have indicated that the exogenous addition of the oligomeric forms of Aβ(1-40)/(1-42) to the extracellular medium leads to the internalization of Aβ in neurons, showing an intraneuronal subcellar distribution between mitochondria, lysosomes/endosomes, and the ER [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The conclusions of this work were revealed to be of extreme importance to understanding the main mechanism implicated in AD pathogenesis since humans and macaque brains share significant similarities [ 18 ]. Additionally, the mechanistic studies performed in different neuronal cell lines have indicated that the exogenous addition of the oligomeric forms of Aβ(1-40)/(1-42) to the extracellular medium leads to the internalization of Aβ in neurons, showing an intraneuronal subcellar distribution between mitochondria, lysosomes/endosomes, and the ER [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sodium azide (NaN 3 ) is used to inhibit energy-dependent endocytosis by disrupting ATP production. The intracellular fluorescence intensity of cells treated with NaN 3 decreased by approximately 26% compared to the control group, confirming that the cellular uptake of rhApoE/Cou-6/Aβ-CN-PMs was moderately energy-dependent [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 82%
“…The various Aβ42 peptides were treated as previously described, with some modifications. 31 Briefly, 1 mg Aβ peptides were combined with HFIP, vortexed for 2 min and incubated overnight at 4 °C with gentle shaking. The Aβ solution was aliquoted and stored at −80 °C after being evaporated in an N 2 flow.…”
Section: Methodsmentioning
confidence: 99%